Effects of seasonal hypoxia on the release of phosphorus from sediments in deep-water ecosystem: A case study in Hongfeng Reservoir, Southwest China. (December 2016) - Wang, Jingfu; Chen, Jingan; Ding, Shiming; Guo, Jianyang; Christopher, Dallimore; Dai, Zhihui; Yang, Haiquan
Abstract: Using the diffusive gradients in thin films (DGT) technique and microelectrode technique, hypoxia and its effects on the release of phosphorus (P) from sediments were carefully investigated in Hongfeng Reservoir, a typical deep-water ecosystem where eutrophication and hypoxia is still an environmental challenge in Southwest China. The results suggested that hypoxia significantly promotes the release of P from sediments and the release of P under hypoxic condition mostly comes from the release of BD–P. Together with the in-situ and high resolution evidences from DGT and microelectrode, the release of P from sediments under hypoxic condition was assumed to be coupled processes which are associated with the combined cycles of "P-Fe-S". Evidences from the present work implied that the internal P-loadings induced by hypoxia, especially after a reduction of external P-loading, should be paid more attention in eutrophic deep-water reservoirs, Southwest China. Highlights: Hypoxia promotes the release of P from sediments in deep-water ecosystem. The release of P from sediments under hypoxic condition mostly comes from the release of BD–P. The release of P from sediments under hypoxia condition is associated with coupled cycles of "P-Fe-S". Abstract : Hypoxia promotes the release of P from sediments in deep-water ecosystem.